Learning Process During Pandemic with CIPP Model on Physical Education - Wilda Welis; Al As'Ari; M. Sazeli Rifki; Syamsuar Syamsuar; Rully Effendi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to evaluate the implementation of Sports and Health Physical Education learning for public elementary schools 120 Pekanbaru City during the Covid-19 pandemic based on the CIPP model (context, input, process, and product). The subject of the study was the principal and teacher of public elementary school 120 Pekanbaru City with total sampling technique. Data collection techniques use observation methods, interviews, questionnaires, and documentation. The data analysis techniques in this study are quantitative and quantitative descriptive analysis. The results showed that the evaluation of the implementation of learning using the CIPP model in Sports and Health Physical Education in public elementary schools 120 Pekanbaru City during the Covid-19 pandemic, namely in the good category, was seen in the average semester report card score, reaching 78.9% in the good category and 21.1% in the very less category. These results show that the online Sports and Health Physical Education learning process is quite effective when viewed from student learning outcomes.